2010
DOI: 10.1177/0363546509352459
|View full text |Cite
|
Sign up to set email alerts
|

Repair versus Reconstruction of the Fibular Collateral Ligament and Posterolateral Corner in the Multiligament-Injured Knee

Abstract: Our series demonstrated a statistically significant higher rate of failure for repair compared with reconstruction of the FCL/PLC. Reconstruction of the FCL/PLC structures is a more reliable option than repair alone in the setting of a multiligament knee injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
240
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(250 citation statements)
references
References 20 publications
7
240
0
3
Order By: Relevance
“…This acute repair strategy was associated with a 38% failure rate and was less successful when compared with a 9% failure rate in more comprehensive reconstructive options with concurrent cruciate ligament reconstruction. Levy et al 15 further reinforced the importance of reconstruction in their systematic review, concluding that reconstruction provides better outcomes than repair of PLC injuries; however, no recommendations were made with regard to the type of reconstruction. Yoon and colleagues 27 compared a nonanatomic fibular sling PLC reconstruction technique with an anatomic-based reconstruction and demonstrated improved Lysholm scores and improved varus and external rotation laxity in the anatomic reconstruction group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This acute repair strategy was associated with a 38% failure rate and was less successful when compared with a 9% failure rate in more comprehensive reconstructive options with concurrent cruciate ligament reconstruction. Levy et al 15 further reinforced the importance of reconstruction in their systematic review, concluding that reconstruction provides better outcomes than repair of PLC injuries; however, no recommendations were made with regard to the type of reconstruction. Yoon and colleagues 27 compared a nonanatomic fibular sling PLC reconstruction technique with an anatomic-based reconstruction and demonstrated improved Lysholm scores and improved varus and external rotation laxity in the anatomic reconstruction group.…”
Section: Discussionmentioning
confidence: 99%
“…13 As a result, reconstruction is recommended for grade III injuries. [13][14][15] The purpose of this article is to describe an anatomic reconstruction technique of the 3 major stabilizers of the PLC using a split Achilles tendon allograft.…”
mentioning
confidence: 99%
“…12 Higher failure rates have been shown with lateral-sided repairs versus reconstruction in the multiligament-injured knee. 13,14 Fig 6. The 9 Â 25emm femoral socket is reamed and tapped, and the calcaneal bone plug is fixed in place with a 7 Â 25emm BioComposite interference screw.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for advocating early surgery in multiligament knee injuries is that the collaterals can be repaired; the repair becomes increasingly difficult two to three weeks after surgery. However, recent literature suggests that reconstruction of the PLC is better than repair, 28,29 and therefore, if one is contemplating a reconstruction, an early surgery is not a necessity. Giannoudis et al 30 reported five cases of knee dislocation with ipsilateral femoral shaft fractures.…”
Section: Management Of the Knee Dislocationmentioning
confidence: 99%